The Ḥarrah's epigraphic heritage: new safaitic inscriptions from the Black Desert in north-eastern Jordan and a Greek inscription referring to Zeus Kyrios. (2nd September 2022) - Al-Manaser, Ali; Norris, Jérôme
Abstract : This paper publishes six new inscriptions discovered at three different sites within the Ḥarrah desert in north-eastern Jordan during the 2017 and 2018 seasons of the BES (Badia Epigraphic Survey). The first text is a five-line Greek inscription referring to the god Zeus Kyrios 'Zeus the Lord' a form of Zeus whose cult was popular in the Ḥawrān and whose name is recognized as masking that of Baalshamin. The text is authored by a person bearing the Arabic theophoric name of Amrosamsos ( Mrʾs²ms¹ ), who describes himself as 'the Goareian', in reference to a district of 'Arabia' mentioned in Greek literary sources. The five Safaitic inscriptions are by nomadic tribesmen from the kin groups of the ʿwḏ and Qmr, some of whom are already known from other Safaitic inscriptions. These texts provide us with two new Safaitic verbs ( ytm 'to become an orphan' and ndy ' to invoke'), as well as with the first example of a member of the ʿwḏ tribe who refers to his service in a ms¹rt ' military unit'.